Transcriptome-Based Analysis of Dof Family Transcription Factors and Their Responses to Abiotic Stress in Tea Plant (Camellia sinensis). (31st October 2016) - Li, Hui; Huang, Wei; Liu, Zhi-Wei; Wang, Yong-Xin; Zhuang, Jing
Abstract : Tea plant ( Camellia sinensis (L.) O. Kuntze) is affected by abiotic stress during its growth and development. DNA-binding with one finger (Dof) transcription factors (TFs) play important roles in abiotic stress tolerance of plants. In this study, a total of 29 putative Dof TFs were identified based on transcriptome of tea plant, and the conserved domains and common motifs of these CsDof TFs were predicted and analyzed. The 29 CsDof proteins were divided into 7 groups (A, B1, B2, C1, C2.1, C2.2, and D2), and the interaction networks of Dof proteins in C. sinensis were established according to the data in Arabidopsis . Gene expression was analyzed in "Yingshuang" and "Huangjinya" under four experimental stresses by qRT-PCR. CsDof genes were expressed differentially and related to different abiotic stress conditions. In total, our results might suggest that there is a potential relationship between CsDof factors and tea plant stress resistance.